2019
DOI: 10.1177/0954410019832127
|View full text |Cite
|
Sign up to set email alerts
|

Flight phase and altitude-dependent geometrical vertical flight plan optimization minimizing the total number of vertical plan segments

Abstract: This paper presents a new method for the geometrical construction of an optimal vertical flight plan associated to a provided lateral flight plan defined as a succession of waypoints characterized by their along-the-track distance relative to the first waypoint and their constraints. The principal objective of the proposed method is the minimization of the total number of vertical flight plan segments, whose slope values closest match the values set for their corresponding flight phase and altitude. The main a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…With the substantial increase in carbon dioxide (CO 2 ) emissions into the atmosphere over the past several years [1,2], the aerospace sector has to limit its figures in the near future [3,4]. For that, some solutions are available, such as working on trajectories optimization [5][6][7][8][9][10] or improving aircraft models to design reliable flight simulators [11][12][13][14]. It has been shown that trajectory optimization can save up to 2% of the cost of flights.…”
Section: Introductionmentioning
confidence: 99%
“…With the substantial increase in carbon dioxide (CO 2 ) emissions into the atmosphere over the past several years [1,2], the aerospace sector has to limit its figures in the near future [3,4]. For that, some solutions are available, such as working on trajectories optimization [5][6][7][8][9][10] or improving aircraft models to design reliable flight simulators [11][12][13][14]. It has been shown that trajectory optimization can save up to 2% of the cost of flights.…”
Section: Introductionmentioning
confidence: 99%
“…Geometrical approaches to vertical flight trajectory optimisation are presented in refs. [53,54]. Yu and Zhang (55) presented a survey of Unmanned Aerial System (UAS) flight path planning approaches.…”
Section: Introductionmentioning
confidence: 99%